Midrimax — new features in the preoperative preparation of patients - E. S. Knyazeva; D. V. Kashperskaya (Oftalʹmologiâ, 2014)
The investigation of the drug Midrimax in order to assess its efficacy and safety in the preoperative preparation for cataract surgery. It is established that the drug causes long-lasting mydriasis in a short period of time, does not affect the level of intraocular pressure. Patients receiving continuous therapy with antihypertensive drugs, there is no increase in blood pressure and heart rate.thus, the Midrimax can be used in patients with chronic diseases in the compensation stage, including in patients with glaucoma.